Blockchain Value Transforming Business Models, Society, and Communities. - Mack, Olga V. (Issn Ser., 2020)
This book focuses on the values of blockchain across industries. Among other things, it explores how blockchain technology adds value to data management, security, and sharing as well as ownership, property, collaboration, and trust. It also explores the possibilities of the Blockchain-as-a-Service (BaaS), digital goods or dGoods, and the transformative power of small acts and micropayments.